A simple integrated microfluidic device for the multiplexed fluorescence-free detection of Salmonella enterica. Issue 3 (14th December 2015) - Strachan, Briony C.; Sloane, Hillary S.; Houpt, Eric; Lee, Jacob C.; Miranian, Daniel C.; Li, Jingyi; Nelson, Daniel A.; Landers, James P.
Abstract : The integration of PCR with a particle-based method for visual DNA detection allows sequence-specific detection of bacterial targets in less than 35 minutes. Abstract : Rapid, inexpensive and simplistic nucleic acid testing (NAT) is pivotal in delivering biotechnology solutions at the point-of-care (POC). We present a poly(methylmethacrylate) (PMMA) microdevice where on-board infrared-mediated PCR amplification is seamlessly integrated with a particle-based, visual DNA detection for specific detection of bacterial targets in less than 35 minutes. Fluidic control is achieved using a capillary burst valve laser-ablated in a novel manner to confine the PCR reagents to a chamber during thermal cycling, and a manual torque-actuated pressure system to mobilize the fluid from the PCR chamber to the detection reservoir containing oligonucleotide-adducted magnetic particles. Interaction of amplified products specific to the target organism with the beads in a rotating magnetic field allows for near instantaneous (<30 s) detection based on hybridization-induced aggregation (HIA) of the particles and simple optical analysis. The integration of PCR with this rapid, sequence-specific DNA detection method on a single microdevice presents the possibility of creating POC NAT systems that are low cost, easy-to-use, and involve minimal external hardware.